MO065TUBULAR EPITHELIAL CELL POLYPLOIDIZATION IS REQUIRED TO SURVIVE AKI BUT PROMOTES CKD DEVELOPMENT. (6th June 2020) - De Chiara, Letizia; Lazzeri, Elena; Angelotti, Maria Lucia; Conte, Carolina; Peired, Anna Julie; Antonelli, Giulia; Melica, Maria Elena; Mazzinghi, Benedetta; Lasagni, Laura; Romagnani, Paola
Abstract: Background and Aims: Acute kidney injury (AKI) is a global health concern. If not lethal in the acute phase, AKI is considered reversible based on the capacity of surviving tubular cells (TECs) to re-enter cell cycle. However, even mild AKI episodes carry a substantial risk of developing chronic kidney disease (CKD). The pathophysiological basis for this phenomenon remains unclear. Recently, we demonstrated that tubular epithelial cells (TECs) can undergo endoreplication-mediated hypertrophy after AKI. Endoreplications are incomplete cell cycles that lead to the formation of polyploid cells. As polyploid cells can provide increased cell function without restoring tissue integrity, we hypothesized that this mechanism is essential to survive AKI but it can be potentially maladaptive. Method: To address this hypothesis, we employed a series of in vitro and in vivo transgenic models based on the Fluorescence Ubiquitin Cell Cycle Indicator (FUCCI) technology to monitor cell cycle phasing in combination with YAP1 overexpression or downregulation. In the in vivo models, YAP1 overexpressing mice and YAP1 knock-out mice were subjected to unilateral ischemia reperfusion injury (IRI) or glycerol-induced rhabdomyolysis to induce AKI. Polyploid cells have been then characterized by microarray analysis, cell sorting, super-resolution STED microscopy and transmission electron microscopy. Results: In vitro, human renal tubular cells undergo polyploidization. The fraction of polyploid cells significantly decreases when YAP1 nuclear translocation is blocked, suggesting a possible involvement of YAP1 in regulating TEC polyploidization. After AKI in mice, the inhibition of YAP1 significantly reduces the number of polyploid cells and worsens kidney function resulting in a dramatic decrease of mouse survival. In contrast, YAP1 overexpression leads to an increase in the number of polyploid cells up to 20% of all TECs, further confirming the role of YAP1 in controlling TEC polyploidization. In YAP1 overexpressing mice, electron microscopy and STED analysis revealed the presence of both mononucleated and binucleated polyploid cells. Strikingly, these mice appear to be more prone to develop tubulointerstitial fibrosis acquiring a marked senescent phenotype along with significant decline in renal function thus suggesting an association between polyploidization and CKD development. Indeed, isolation of polyploid cells proved that these cells actively transcribe and secrete pro-fibrotic and senescent factors confirming their role in CKD progression. Conclusion: These data suggest that: 1) polyploidization after AKI is required to preserve renal function in the acute phase of damage and it is essential for survival 2) polyploid cells are pro-fibrotic and senescent leading in the long run to the progression of AKI to CKD.